Analysis of International Disputes over Digital Services Tax and Exploration of China’s Approach - Tang, Siyuan (Transactions on Economics, Business and Management Research, 2024)
With the continuous emergence of emerging information technologies, the digital economy is developing rapidly around the world. The global operations of multinational digital enterprises no longer rely on physical presence. The effectiveness of permanent establishment rules based on the traditional real economy settings has been questioned by market countries, which actively participate in Market countries where digital business value is created do not receive corresponding taxation rights. Multinational digital companies take advantage of loopholes in digital platforms and current tax rules to actively carry out tax planning, resulting in digital companies’ global tax burden being much lower than that of traditional companies. Tax sources cannot be fairly and reasonably distributed in the places where value is created and profits are taxed, which harms the tax interests of market countries. Against the background of slow progress in the OECD global unified solution, as a temporary unilateral measure to address the challenges of the digital economy, some countries have taken the lead in imposing digital service taxes on specific digital businesses of digital enterprises. On the basis of discussing the relevant concepts and theories of digital service tax, this article discusses the relevant concepts and theories of digital service tax, and analyzes the international development of digital service tax and the positions of various countries around the world. Further analyze the impact of digital service tax collection from three aspects: national fiscal revenue, tax trade disputes and international tax order coordination, and analyze the impact of digital service tax on digital enterprises. Then the perspective is focused on my country, sorting out and summarizing my country’s relevant digital economy tax policies, and analyzing the impact of digital service tax on my country in the near term and long term based on the development of my country’s digital economy. Finally, based on the previous comparative analysis and impact analysis, my country’s tax system for promoting the development of the digital economy has gradually improved and actively participated in the reshaping of international tax rules, and my country’s response strategies under the digital service tax have been proposed. The different levels of digital economic development between China and countries that have levied digital service taxes will inevitably lead to disharmony in the international tax order. The study found that the fiscal revenue brought by digital service tax is limited and has a certain degree of distortion effect. It is necessary to actively participate in international cooperation and make China’s voice heard before reaching a consensus on international tax rules. In the long term, we should focus on the connection between the two-pillar plan and the domestic tax system, strengthen tax information exchange, improve the domestic digital tax rule system, and promote the healthy and sustainable development of my country’s digital economy.